Technical change and total factor productivity growth for Chinese provinces: a panel data analysis - Alice Shiu; Almas Heshmati (Institute for the Study of Labor (IZA), 2006)
We present in this paper the panel econometrics estimation approach of measuring the technical change and total factor productivity (TFP) growth of 30 Chinese provinces during the period of 1993 to 2003. The random effects model with heteroscedastic variances has been used for the estimation of the translog production functions. Two alternative formulations of technical change measured by the single time trend and the general index approach are used. Based on the measures of technical change, estimates of TFP growth could be obtained and its determinants were examined using regression analysis. The parametric TFP growth measure is compared with the non-parametric Solow residual. TFP has recorded positive growth for all provinces during the sample period. Regional breakdown shows that the eastern and central regions have higher average TFP growth when compared with the western region. Foreign direct investment (FDI) and information and communication technology (ICT) investment are found to be significant factors contributing to the TFP difference. While these two factors are found to have significant influence on TFP, their influence on production is relatively small compared to traditional inputs of production.
Keywords: C23; D24; E22; O18; O47; 330; technical change; TFP growth; provinces; China; ICT; FDI; infrastructure; Technischer Fortschritt; Produktivität; Regionales Wachstum; Technologie; Zeitreihenanalyse; Schätzung; China